2017
DOI: 10.1007/s40124-017-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

Childcare in Infancy and Later Obesity: a Narrative Review of Longitudinal Studies

Abstract: Purpose of ReviewThe purpose of this review was to summarize the current literature on the longitudinal relationship between non-parental childcare during infancy and later obesity.Recent FindingsEleven studies met the inclusion criteria, comprising 74 associations relevant to the review. Studies were highly heterogeneous in terms of defining childcare, categorizing different types of childcare, assessing obesity, and age at measurement of outcome and exposure. Most of the associations were either non-signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Additionally, infants who spent time in multiple types of care contributed to each exposure. We adjusted for covariates that were of a priori interest based on prior literature, 7 including infant age, gender, race, birth weight for gestational age z-score, breastfeeding duration, and early introduction of solid foods (before 4 months of age); maternal age, education, marital status, and prepregnancy BMI; and household income. We report adjusted estimates per each additional 10 hours of care each week.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, infants who spent time in multiple types of care contributed to each exposure. We adjusted for covariates that were of a priori interest based on prior literature, 7 including infant age, gender, race, birth weight for gestational age z-score, breastfeeding duration, and early introduction of solid foods (before 4 months of age); maternal age, education, marital status, and prepregnancy BMI; and household income. We report adjusted estimates per each additional 10 hours of care each week.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Child care has been inconsistently associated with obesity in children younger than 6 years. [5][6][7][8] Among infants, previous studies have also found mixed results. [9][10][11][12][13][14][15][16][17][18] In our prior review of 11 articles examining child care during infancy and later obesity, we found that studies were heterogeneous in defining child care, categorizing child care, and measuring both exposure and outcome.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Namely because healthy behaviours and obesogenic trajectories are established early in life (3,(6)(7)(8)(9)(10)(11)(12)(13) and a rising number of children attend out-of-home childcare, with many starting as early as the first year of life and spending much of their week days in these settings. (14)(15)(16) Two recent reviews have summarised the literature on the association between exposure to childcare, one between ages 0-2 years (17) and one between ages 0-5 years, (18) and obesity risk. Both these publications found that available evidence is limited to cross-sectional and short-term follow-up studies, with most studies either revealing no association or a harmful effect.…”
Section: Introductionmentioning
confidence: 99%